2021
DOI: 10.56499/jppres21.1015_9.5.609
|View full text |Cite
|
Sign up to set email alerts
|

The α-mangostin effect on the quantity of TGF-β1 titer relate to the mandibular bone volume of Rattus novergicus in the periodontitis model

Abstract: Context: Periodontitis causes pocket formation, gingival recession, and destruction of periodontal ligaments and alveolar bone. Periodontitis disturbs the attachment of periodontal ligaments to the maxillary and mandibular bones. The α-mangostin has shown role-playing in the bone remodeling process. Aims: To evaluate the potential of α-mangostin induce the TGFβ1 titer associated with the increased mandibular bone volume on the alveolar bone remodeling of periodontitis of Rattus novergicus. Methods: The α-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…This is due to the presence of macrophages stimulated by flavonoids, resulting in the increased expression of TGF-β. 19 The increase in TGF-β following mangosteen peel extract treatment found in this study was also identified in a study examining the effect of alpha mangosteen on the quantity of TGF-β1 titter in periodontitis. In the study, alpha mangosteen hydrogel was applied to the entire area of the damaged and sutured Rattus norvegicus mandibular bone.…”
Section: Resultssupporting
confidence: 72%
“…This is due to the presence of macrophages stimulated by flavonoids, resulting in the increased expression of TGF-β. 19 The increase in TGF-β following mangosteen peel extract treatment found in this study was also identified in a study examining the effect of alpha mangosteen on the quantity of TGF-β1 titter in periodontitis. In the study, alpha mangosteen hydrogel was applied to the entire area of the damaged and sutured Rattus norvegicus mandibular bone.…”
Section: Resultssupporting
confidence: 72%
“…The finding showed that EGCG inhibits the process of alveolar bone damage through RANKL, 10 TNF-α, 11 and increases osteoprotegerin (OPG), 10 RANK, 10,11 and IL-10. 11,12 The effect is similar to α-mangosteen, which is able to stimulate some growth factors like tumor growth factor-β, 13 and TRAP5b 14 and also inhibit the growth of etiological bacteria 15,16 and RUNX2. 14 Periodontitis is a disease of the periodontal tissues that is characterized by damage to the ligaments and surrounding alveolar bone.…”
Section: Introductionmentioning
confidence: 94%